Influence of heat treatment on the microstructure, wettability, and corrosion resistance of a Ti–30Nb–7Zr alloy used in biomedical applications - Emília dos Santos Monteiro; Carlos Nelson Elias; Francielly Moura de Souza Soares; Késia Simões Ribeiro; Ana Isabel de Carvalho Santana; Claudinei dos Santos (Journal of Materials Research and Technology, 2024)
Commercially pure titanium (cp Ti ASTM F67) and the Ti–6Al–4V ELI (Extra Low Interstitial) alloy (ASTM F136) are commonly used as biomaterials due to their biocompatibility, mechanical strength, and corrosion resistance. The low mechanical resistance of cp Ti reduces its applications. The F136 alloy may release toxic ions (Al and V). Moreover, the fact that the elastic modulus of the F136 is larger than the bone leads to stress shielding and induces bone loss. These factors drive research towards the development of new biomedical metal alloys with more suitable mechanical properties. β titanium and β-metastable alloys have special attention as potential alternatives to the F136 alloy applications. This work aimed to analyze the microstructure, wettability, and corrosion resistance of the β Ti–30Nb–7Zr alloy before and after heat treatment, and compare the results with those for the F136 alloy. The β Ti–30Nb–7Zr is an alloy based on non-toxic elements and with a smaller elastic module than F136. The techniques of open circuit potential, potentiodynamic polarization, potentiostatic polarization, and electrochemical impedance spectroscopy were used. The results of this work showed that the Ti–30Nb–7Zr alloy in the as-received condition had a β matrix with precipitates, and after recrystallization heat treatments, the precipitates were eliminated. The Ti–30Nb–7Zr alloy heat treated at 500 °C for 30 min had α phase precipitates, which increased the surface energy and decreased the corrosion resistance. The best corrosion resistance was observed in Ti–30Nb–7Zr after heat treatment at 900 °C for 1 h. The conclusion is that after adequate heat treatment, the Ti–30Nb–7Zr alloy is an alternative to Ti–6Al–4V for biomedical applications.